Verifying Usage of Thermoelectric Peltier as an Electric Generator for Electric Vehicle - Shahrudin, Muhammad Afif Firdaus; Ahmad, Md Zarafi (Evolution in Electrical and Electronic Engineering, 2024)
In this study, an experiment is conducted to verify usage of thermoelectric Peltier as an electric generator for electric vehicles using heat converting to electric conversion. The study successfully shown a production of electric by emphasizing the potential of thermoelectric to generate electric. Experiment has performed and exhibited efficacy in generating voltage and current to facilitate the production of electricity. Nevertheless, there were several restrictions, such as the constrained positioning of the Peltier unit, small-scale testing, and the exclusion of other possible materials’ heat conductivity. Besides, the studies are to examine generation in order to generate electric for electric vehicles and improving by mere more research. The goal of the study was to demonstrate sustainable power production systems that uses Peltier modules to utilise thermoelectric conversion and are efficient. The greatest temperature differences and material research on the Peltier semi-conductor are among the suggested enhancements. These recommendations seek to improve the main line of knowledge and advance the efficient and higher production of electric from heat difference conversion to electricity.